2021
DOI: 10.1088/1361-6463/abf373
|View full text |Cite
|
Sign up to set email alerts
|

Inverse design of structured materials for broadband sound absorption

Abstract: This paper discusses the design of structured materials for broadband waterborne sound absorption. The structured materials are composed of a rubber matrix embedded periodically with cavities. To find the optimal distribution of cavities, an inverse design method based on topology optimization is proposed. Structured materials with novel hybrid cavities are thus designed. Efficient absorption over a wide frequency range between 600 Hz and 8000 Hz is achieved. The underlying mechanism behind the broadband absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…From the current research on broadband absorption, the trend of sidewall limitation can be observed from most broadband optimization procedures, e.g. [20] and [41]. In contrast, the absorption of sound waves by MAM mainly depends on the high energy dissipation at the connection between the film and the rigid body [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the current research on broadband absorption, the trend of sidewall limitation can be observed from most broadband optimization procedures, e.g. [20] and [41]. In contrast, the absorption of sound waves by MAM mainly depends on the high energy dissipation at the connection between the film and the rigid body [33].…”
Section: Resultsmentioning
confidence: 99%
“…air-filled cavities [7][8][9][10][11][12][13][14], glass beads [15], piezoelectric patches [16], or locally resonant phononic crystals [17][18][19], are embedded in rubbery coatings to promote scattering and wave mode conversion, and thus to strengthen the sound energy dissipation. Among them, air-filled cavities, as the earliest utilized scatterer, can be easily fabricated and exhibit excellent underwater sound absorption performance, causing considerable interests in the field of underwater acoustic materials science [20,21]. However, the outstanding sound absorption performance only appear near the resonant frequency of the cavity or in the higher frequency band, and a sound absorption valley usually appears after the first resonant frequency, which limits its application in broadband sound absorption.…”
Section: Introductionmentioning
confidence: 99%
“…To reverse engineer acoustic coatings with embedded voids to achieve desired acoustic performance, metaheuristic optimization techniques such as genetic algorithms (GA) (Meng et al 2012a;Yuan et al 2019;Chang et al 2005;Wang et al 2021) and evolutionary algorithms (EA) (Romero-García et al 2009;Zhao et al 2018) are widely used. Interest has been given to GA as it can be used to find a near-optimal solution efficiently (Meng et al 2012a;Yuan et al 2019;Chang et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To reverse engineer acoustic coatings with voids to achieve desired acoustic performance, metaheuristic optimization techniques such as genetic algorithms (GA) [14,25,26,27] and evolutionary algorithms (EA) [28,29] are widely used. Particular interest has been given to GA as it can be used to find a near-optimal solution efficiently [14,25,26].…”
Section: Introductionmentioning
confidence: 99%